Imagining the city in lockdown: Place in the COVID-19 self-recordings of the Lothian Diary Project - Cowie, Claire; Hall-Lew, Lauren; Elliott, Zuzana; Klingler, Anita; Markl, Nina; McNulty, Stephen Joseph (Frontiers in Artificial Intelligence, 2022)
The COVID-19 pandemic brought about a profound change to the organization of space and time in our daily lives. In this paper we analyze the self-recorded audio/video diaries made by residents of Edinburgh and the Lothian counties during the first national lockdown. We identify three ways in which diarists describe a shift in place-time, or “chronotope”, in lockdown. We argue that the act of making a diary for an audience of the future prompts diarists to contrast different chronotopes, and each of these orientations illuminates the differential impact of the COVID-19 lockdowns across the community.